PORTARIA PRR2 Nº 219, DE 17 DE DEZEMBRO DE 2014 - Jose Augusto Simoes Vagos (DMPF-e de 22/12/2014, n. 236, Extrajudicial, p. 164-165, 2014)
Designa Procuradores Regionais para atuar no plantão judicial do 1º semestre de 2015.